Long-term stability of mechanically exfoliated MoS2 flakes. (28th September 2017) - Budania, Prachi; Baine, Paul; Montgomery, John; McGeough, Conor; Cafolla, Tony; Modreanu, Mircea; McNeill, David; Mitchell, Neil; Hughes, Greg; Hurley, Paul
Abstract: Abstract : The long-term stability of mechanically exfoliated MoS2 flakes was compared for storage in the air and storage under vacuum. Significant changes in MoS2 flakes were observed for samples stored in the air, whereas similar flakes on samples stored in vacuum underwent no change. Small speckles were observed to appear on the surface of flakes stored in the air, followed by thinning and eventual decomposition of MoS2 flakes. The speckles are suspected to be formed by oxidation of MoS2 in the presence of atmospheric oxygen and water molecules, resulting in the formation of hydrated MoO3 .